Economic efficiency of public secondary education expenditure: how different are developed and developing countries? (2017)
This study measures the efficiency of public secondary education expenditure in 35 developing and developed countries using a two-step semi-parametric DEA (data envelopment analysis) methodology. First, we implement two cross-country frontier models for the 2009-2012 period: one using a physical input (i.e., teacher-pupil ratio) and one using a monetary input (i.e., government expenditure per secondary student). These results are corrected by the effects of GDP per capita and adult educational attainment as non-discretionary inputs. We obtain four important results: (i) developed and developing countries have the same education production processes when they are compared using physical inputs but not when compared using monetary inputs; (ii) developing countries could increase their enrollment rates and PISA scores by approximately 9% and 5%, respectively, by maintaining the same teacher-pupil ratios and public spending levels as developed countries; (iii) Ireland, Japan and Korea are efficient countries in the two frontier models (Colombia is also included in this category when the teacher-pupil ratio is used as input); and (iv) robust empirical evidence indicates that both income and parental educational attainment positively affect the efficiency of public education in both models.